مصطلحات فن الخط العربي الإسلامي - أد/ نادية لقجع جلول سايح (Journal of Calligraphy, 2021)
Arabic calligraphy is one of the most prominent and highest Islamic arts because of its connection with the Holy Qur’an, or more accurately because it is linked to the drawing of the Noble Qur’an, that is, by the way of writing its words as drawn by the “Book of Revelation”, and thus enjoys a unique symbolism in Islamic civilization, and because it is a civil industry, it strengthens with the power of civilization. It is weakened by its weakness, and because it is a creative faculty, calligraphers, artists and writers have mastered the diversity of its forms, and because it is an independent art by itself, a unified idiomatic base has been formed that brings together everyone who wants to study this art as a unique field of knowledge. As we try, through this research, to combine with the explanation the terms of Arabic calligraphy, we in fact present a living model and conclusive evidence of the richness of the aesthetic of Arabic license.